Densities and phase equilibria of hydrogen, propane and vegetable oil mixtures. Experimental data and thermodynamic modeling - Hegel, Pablo Ezequiel (2017)
Heterogeneous catalytic gas-liquid reactions are intensified when carried out in the homogenous fluid phase by means of a supercritical co-solvent. For instance, supercritical propane is used to enhance yield in the hydrogenation of vegetable oils. Besides phase equilibrium knowledge, volumetric information is also needed to elucidate kinetic mechanisms and design continuous supercritical reactors. In this work, we report new experimental PvT data of the reactive mixture H2+sunflower oil+propane using the isochoric method. In addition, the phase equilibria and PvT data are modeled with the GCA and RK-PR equations of state, respectively. The isochoric method not only provides PvT information under the reaction conditions, but also the reactive system compressibility, key variable to attain enhanced transport properties in the supercritical reactors.